PENGARUH pH DAN LAMA PENYIMPANAN TERHADAP STABILITAS KIMIA STANDAR (+)-KATEKIN - Leliqia, Ni Putu Eka; Purwitadewi, Yanita Ristanti; Wirasuta, I Made Agus Gelgel (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 5 (2015): Indonesian Journal of Legal and Forensic Sciences, 2015)
(+)-Catechin was a potential compound to be isolated and developed into natural antioxidant product, but it was unstable because it was easy to be oxidized and formed quinone metabolite. This became a problem in its development and isolation process. Factors that can influence the oxidation process of (+)-catechin were pH condition and storage time. Therefore, this research was conducted to know pH and storage time influence towards the (+)-catechin stability. Observation was done in two parameters which was the acid-base pH (pH 1,64-10) and the storage time for 8 days. The influence of both the parameters towards (+)-catechin standard stability was observed by the quinone metabolite formation from (+)-catechin oxidation reaction result. (+)-catechin was declared as unstable if quinone metabolite was formed by absorbance measurement in its maximum wavelength, 409nm with spectrophotometry method. The obtained result showed that (+)-catechin standard was stable in pH 1.64-6 for 8 days storage and was unstable in pH 7-10 showed by the formation of quinone metabolite for 2-8 days storage.